2017
DOI: 10.2147/ijn.s132719
|View full text |Cite
|
Sign up to set email alerts
|

ATP synthesis in the energy metabolism pathway: a new perspective for manipulating CdSe quantum dots biosynthesized in <em>Saccharomyces cerevisiae</em>

Abstract: Due to a growing trend in their biomedical application, biosynthesized nanomaterials are of great interest to researchers nowadays with their biocompatible, low-energy consumption, economic, and tunable characteristics. It is important to understand the mechanism of biosynthesis in order to achieve more efficient applications. Since there are only rare studies on the influences of cellular energy levels on biosynthesis, the influence of energy is often overlooked. Through determination of the intracellular ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The downstream metabolites of hydrogen selenide are multiple organoselenium compounds, including selenocysteine (SeCys), L-selenocystine [(Cys-Se) 2 ] and selenomethionine (SeMet) (Fig. 2 ); this has been confirmed in Saccharomyces cerevisiae cells by high-performance liquid chromatography coupled with inductively coupled plasma mass spectrometry analysis and the use of selective selenol probes [ 5 , 8 , 9 ]. The consumption of GSH induces the upregulation of the expression of cysteine-synthesis-related genes, which can promote the conversion of SeMet to SeCys [ 10 ].…”
Section: How To Synthesize Designer Nanocrystals In Live Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…The downstream metabolites of hydrogen selenide are multiple organoselenium compounds, including selenocysteine (SeCys), L-selenocystine [(Cys-Se) 2 ] and selenomethionine (SeMet) (Fig. 2 ); this has been confirmed in Saccharomyces cerevisiae cells by high-performance liquid chromatography coupled with inductively coupled plasma mass spectrometry analysis and the use of selective selenol probes [ 5 , 8 , 9 ]. The consumption of GSH induces the upregulation of the expression of cysteine-synthesis-related genes, which can promote the conversion of SeMet to SeCys [ 10 ].…”
Section: How To Synthesize Designer Nanocrystals In Live Cellsmentioning
confidence: 99%
“…Unlike the conventional chemical synthesis, which mostly occurs at ∼200–300°C, ARLCS proceeds in ambient physiological conditions. Thus, it is of significance to investigate the underlying energy driving the reactions [ 8 , 14 ]. ATP is the commonest direct energy resource in live cells.…”
Section: How To Synthesize Designer Nanocrystals In Live Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of microorganism genome sequences could considerably increase the range of possibilities in genetic manipulation of microorganism to implement the nanoparticles biosynthesis and the in vivo tuning of nanoparticle characteristics. A recent example has come from the study of Zhang et al (2017), which showed how CdSe quantum dots biosynthesis can be improved through genetic modification of the ATP metabolism pathway in yeast S. cerevisiae [107]. Biotechnological approaches based on genetic engineering and recombinant technologies could allow the identification of sequences of gene involved in nanoparticle synthesis and a possible heterologous expression (i.e., controlled expression of one or more gene sequences in a host organism) to enhance nanomaterial production efficiency [91].…”
Section: Biochemistry Molecular Biology and Geneticsmentioning
confidence: 99%